Pengaruh Struktur Modal, Likuiditas, Pertumbuhan Penjualan, dan Green Accounting Terhadap Profitabilitas - Shakila Dewi Maharani; Desy Mariani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of capital structure, liquidity, sales growth, and green accounting, assessed through environmental performance and environmental costs, on the profitability of companies. The research focuses on the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, which represents one of the most dynamic and environmentally impactful industries in Indonesia. The sample consists of 30 companies selected using a purposive sampling technique based on predetermined criteria, ensuring the representativeness and relevance of the data analyzed. The study employs multiple linear regression analysis using SPSS version 22.0 to test the hypotheses and measure the extent to which the independent variables contribute to profitability as the dependent variable. The findings reveal that liquidity and sales growth exert a positive and significant influence on profitability, indicating that firms with higher liquidity levels and stronger sales growth are better positioned to enhance their financial performance. In contrast, capital structure demonstrates a negative and significant effect, suggesting that higher levels of debt reduce profitability due to increased financial burdens. Similarly, green accounting, when assessed through environmental performance, also shows a negative and significant impact, implying that companies focusing on environmental initiatives may face higher costs that suppress short-term profitability. However, green accounting as measured by environmental costs does not show any significant effect on profitability, highlighting that disclosure or allocation of environmental costs alone may not directly translate into financial outcomes. Overall, the study concludes that capital structure, liquidity, sales growth, and green accounting—when measured through both environmental performance and costs—jointly influence the profitability of food and beverage companies on the IDX during the observed period.